2020
DOI: 10.1292/jvms.19-0587
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiological survey and phylogenetic analysis of bovine respiratory coronavirus in Japan from 2016 to 2018

Abstract: Bovine coronavirus (BCoV) is an etiological agent of bovine respiratory disease (BRD). BRD is a costly illness worldwide; thus, epidemiological surveys of BCoV are important. Here, we conducted a molecular epidemiological survey of BCoV in respiratory-diseased and healthy cattle in Japan from 2016 to 2018. We found that 21.2% (58/273) of the respiratory-diseased cattle were infected with BCoV. The respiratory-diseased cattle had virus amounts 4.7 times higher than those in the asymptomatic cattle.Phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…BCoV infection is initiated by HE and S protein attachment to target tissues and both are important for BCoV pathogenesis [11][12][13]. The hypervariable region of the S protein is used to determine the genetic variability and evolution of BCoV viruses, and S protein sequence alignments are important in evaluating novel variants of BCoV strains [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…BCoV infection is initiated by HE and S protein attachment to target tissues and both are important for BCoV pathogenesis [11][12][13]. The hypervariable region of the S protein is used to determine the genetic variability and evolution of BCoV viruses, and S protein sequence alignments are important in evaluating novel variants of BCoV strains [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, from our analysis of the association of microorganisms and metabolites, we found that non-dominant microorganisms also had strong associations with non-dominant metabolites. BRD is a multifactorial disease and a mixed infection by multiple pathogenic microorganisms can lead to metabolic disorders of organisms [ 8 ]. Due to the diversity and complexity of the microbial ecosystem, we only analyzed dominant microbes and metabolites at present.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, pathogen infection and respiratory microbial imbalance are important causative factors [ 4 , 5 , 6 ]. The viral pathogens most often identified are Bovine herpesvirus type 1 , Bovine parainfluenza-3 , Bovine coronavirus , and Bovine viral diarrhea virus [ 7 , 8 ], while common bacterial pathogens include Mannheimia haemolytica , Pasteurella multocida , Histophilus , and Mycoplasma [ 9 , 10 ]. Increasing evidence suggests the importance of pathogens encountering the resident microbiota and other pathogens while colonizing the host.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, recent studies report that BCoV is also considered as a key pathogen associated with respiratory diseases [47][48][49][50][51]. Except for the KOR, other countries have focused on BCoV as a respiratory pathogen rather than as a diarrheal pathogen [52][53][54][55]. Further study is required to explore the prevalence of BCoV by its associations with various clinical symptoms and to identify the genetic characteristics between enteric and respiratory BCoVs circulating in the KOR.…”
Section: Discussionmentioning
confidence: 99%